Effects of lactic acid and herbal blend as antibiotic alternatives on growth, carcass traits, blood chemistry, and microbial load in broiler chickens - Elwy A. Ashour; Saad A. Al-Ardhi; Mohamed E. Abd El-Hack; Ahmed I. Elsherbeni; Ahmed A. Elolimy; Mahmoud Madkour; Vincenzo Tufarelli; Ayman A. Swelum (Poultry Science)
The objective of the current study was to estimate the beneficial effects of lactic acid (LA) and an herbal mixture (HM) as alternatives to antibiotics in broilers’ diets, focusing on different growth performance (GP) traits, carcass characteristics, blood biochemistry, besides the microbial load of intestinal. In a fully randomized design, A total number of 360 - unsexed - broiler chicks (Ross 308 strain) at the age of one day, were divided into six experimental groups. Every group was further divided into 6 replicates (10 chicks per replicate). The treatments included: NC group (birds fed standard diet only), PC (birds fed standard diet + antibiotic Colistin® at a level of 0.5 g /kg), LA2, LA4 (standard diet + LA at levels of 2 and 4 cm³ /kg, respectively), and HM2, HM4 (standard diet + HM at levels of 2 and 4 g /kg, respectively). The HM was composed of: 300 g of thyme powder (Thymus vulgaris), 300 g of hot red pepper (Capsicum annuum), 300 g of rosemary (Salvia rosmarinus), 150 g of anise (Pimpinella anisum), 150 g of spearmint (Mentha spicata), 300 g of black cumin seed (Nigella sativa), and 300 g of garlic powder (Allium sativum). A nonsignificant (p > 0.05) differences were detected in broiler live body weight (LBW) among the treatments. However, there was substantial improvement (P < 0.05) in daily body weight gain (DBWG) in the 22-32-day period. Feed intake (FI) and feed conversion ratio (FCR) were also significantly influenced (P < 0.001) during the 22–32-day period and across the entire 1–32-day experimental period. Although absolute spleen and gizzard weights were significantly enhanced (P < 0.05), other carcass traits were unaffected. Serum biochemical indices and antioxidant enzyme activities were remarkably improved (P < 0.001, and P < 0.05) across all treatment groups. Additionally, supplementation with these feed additives significantly impacted caecal microbial load, the HM4 group displayed the highest scores of total bacterial counts (TBC) and Lactobacilli. Overall, the supplementation of lactic acid (LA4) and the herbal mixture (HM4) enhanced blood parameters, antioxidant activity, and gut bacterial counts, thereby promoting optimal broiler performance.